O NEPRE e a implementação da Lei 10.639/03 no estado de Mato Grosso - Gonçalves, Vanda Lúcia Sá (2015)
This research has the objective to analyze the implementation of Law 10.639/03 in state of Mato Grosso through the programs of SECAD/ME during the periods from 2009 to 2011, focusing on the continuing formation courses carry out by NEPRE in ambit of federal university of Mato Grosso. These courses in execution, using as strategy the distance education courses which embrace professors from township from all the state. The data used for this analysis in this evaluative research were obtained from the following resources: a) final report cards from the courses; b) c) and the analyses of the documents. It was observed that programs made by SECAD for the implementation of the Law n. º 10.639/03 in state of Mato Grosso have a limited capacity, on one hand, because of the lack of financial resources and , on the other hand, by the not resolution of the problem of the fault of basic formation. This is a problem which cannot be remedied without rethink the model of educational formation in vigor of our society, and, without more investments in the structural bases.